Nation branding of Kuwait versus Saudi Arabia: a comparative thematic content analysis of official tourism Instagram accounts @VisitKuwait and @VisitSaudi.Ar - Alblooshi, Abdullah (My University, 2026)
This thesis examines how Kuwait and Saudi Arabia use their official Arabic-language tourism Instagram accounts to frame their national identity. Despite sharing a common Gulf context, the two countries differ substantially in their global visibility. Drawing on framing theory and Anholt's nation branding competitive identity framework, the thesis conducts a comparative thematic content analysis of 300 posts from @VisitKuwait and @VisitSaudi.Ar, coded using a 12-theme codebook for dominant theme ([alpha] = .857), post format, and audience engagement. Both accounts prioritize events and entertainment but differ in their national identity construction: Kuwait foregrounds patriotism, people, and future-oriented narratives, while Saudi Arabia emphasizes nature, culture, and art. Kuwait generated stronger engagement per post despite its smaller follower base, suggesting thematic focus matters more than scale. People and hospitality theme drove the highest engagement in both accounts, and video reels consistently outperformed photos and carousel formats. The findings offer an empirically grounded, Gulf-specific contribution to nation branding and digital communication research, with actionable implications for Kuwait's tourism strategy.
Keywords: Nation branding; Gulf nations; Thematic comparative; Content analysis; Instagram account